Sex and APOE ε4 genotype modify the Alzheimer’s disease serum metabolome - Matthias Arnold (Nature Portfolio, 2020)
Sex and the APOE ε4 genotype are important risk factors for late-onset Alzheimer’s disease. In the current study, the authors investigate how sex and APOE ε4 genotype modify the association between Alzheimer’s disease biomarkers and metabolites in serum.